Pola Perjalanan Agrowisata Hutan Pinus Pango-pango Di Kabupaten Tana Toraja - Yulicke Gemi Nastiti Manguju; Margarteha Wadid Rante; Andri Machmury; Yenny Susanto (Politeknik Pariwisata Makassar, 2026)
Abstract This study aims: (1) To find out the Potential of Pango-pango Pine Forest Agrotourism in Tana Toraja Regency (2) To find out the Travel Pattern of Pango-pango Pine Forest Agrotourism in Tana Toraja Regency. Data collection in this study was taken using the following techniques: observation, interviews, and documentation, and analyzed using qualitative methods. The results of this study indicate (1) knowing the Potential of Pango-pango Pine Forest Agrotourism in Tana Toraja Regency. (2) The results of the design of the travel pattern of Pango-pango Pine Forest Agrotourism in Tana Toraja are considered feasible but not optimal. Lack of facilities such as souvenir shops, places of worship, and ATV activities still need to be added. However, this travel pattern is an important basis for the development of agrotourism in the future.